Cross‐scale interactions affect tree growth and intrinsic water use efficiency and highlight the importance of spatial context in managing forests under global change. (27th March 2017) - Ruzicka, Kenneth J.; Puettmann, Klaus J.; Brooks, J. Renée
Summary: We investigated the potential of cross‐scale interactions to affect the outcome of density reduction in a large‐scale silvicultural experiment to better understand options for managing forests under climate change. We measured tree growth and intrinsic water‐use efficiency (iWUE) based on stable carbon isotopes (δ 13 C) to investigate impacts of density reduction across a range of progressively finer spatial scales: site, stand, hillslope position and neighbourhood. In particular, we focused on the influence of treatments beyond the boundaries of treated stands to include impacts on downslope and neighbouring stands across sites varying in soil moisture. Trees at the wet site responded with increased growth when compared with trees at the dry site. Additionally, trees in treated stands at the dry site responded with increased iWUE while trees at the wet site showed no difference in iWUE compared to untreated stands. We hypothesized that water is not the primary limiting factor for growth at our sites, but that density reduction released other resources, such as growing space or nutrients to drive the growth response. At progressively finer spatial scales we found that tree responses were not driven by hillslope location (i.e. downslope of treatment) but to changes in local neighbourhood tree density. Synthesis . This study demonstrated that water can be viewed as an agent to investigate cross‐scale interactions as it links processes operating at coarse to finer spatial scales and vice versa. Consequently, management prescriptions such as density reductions to increase resistance and resilience of trees to climate change, specifically to drought, need to consider cross‐scale interactions as specific magnitude and mechanisms of growth responses can only be predicted when multiple scales are taken into account. Abstract : This study demonstrated that water can be viewed as an agent to investigate cross‐scale interactions as it links processes operating at coarse to finer spatial scales and vice versa. Consequently, management prescriptions such as density reductions to increase resistance and resilience of trees to climate change, specifically to drought, need to consider cross‐scale interactions, as specific magnitude and mechanisms of growth responses can only be predicted when multiple scales are taken into account.